History of Yugoslavia - Calic, Marie-Janin (Central European Studies, 2018)
Why did Yugoslavia fall apart? Was its violent demise inevitable? Did its population simply fall victim to the lure of nationalism? How did this multinational state survive for so long, and where do we situate the short life of Yugoslavia in the long history of Europe in the twentieth century? The Complete History of Yugoslavia by Marie-Janine Calic provides a concise, accessible, comprehensive synthesis of the political, cultural, social, and economic life of Yugoslavia-from its nineteenth-century South Slavic origins to the bloody demise of the multinational state of Yugoslavia in the 1990s.